Trends In Academic Content for Mobile Devices [video] - Dan D'Agostino; Sarah Forbes (Partnership: The Canadian Journal of Library and Information Practice and Research, 2012)
This presentation by Sarah Forbes and Dan D'Agostino was given at the Ontario Library Association's Super Conference in Toronto, Ontario, on February 3, 2012.